Ritual, Theology, and Islamic Civilization: The Grebek Besar Tradition in Demak Regency - Kurniawati, Dita; Rosyid, Moh.; Mas'udi, Mas'udi; Sopian, Achmad; Makki, Ahmad (UIN Maulana Malik Ibrahim Malang, 2025)
Within the broader history of Islamic civilization in Java, ritual traditions such as Grebek Besar have functioned as key sites for the transmission, reinterpretation, and embodiment of Islamic ethical and theological values. This study examines the cultural and theological dimensions of the Grebek Besar festival in Demak Regency, Central Java, Indonesia, one of the most significant Islamic cultural events in Java. Rooted in the commemoration of Eid al-Adha, the festival embodies a dynamic synthesis between Islamic doctrine and Javanese cultural expression. Previous studies have largely treated Grebek Besar as a folkloric or historical tradition, without adequately examining its lived-theological meanings as articulated by local religious actors and enacted in everyday ritual practices. Using a qualitative ethnographic approach, this study is based on participant observation, in-depth interviews with religious leaders and community elders, and analysis of local archives and manuscripts. The findings are consolidated into a central thematic claim: Grebek Besar functions as a form of lived Islamic theology in which ritual performances, symbolic objects, and communal participation operate as interconnected mechanisms that sustain religious piety, social cohesion, and cultural continuity among Javanese Muslims. The study demonstrates that the festival is not merely a cultural celebration, but a ritualized space of Islamic devotion embedded in local custom. Processions, communal prayers, and food-sharing practices are shown to carry theological meanings that reinforce the community’s relationship with God while affirming collective historical memory and identity. This research makes a specific scholarly contribution by proposing an empirically grounded framework of “lived theology” in Javanese Islam, bridging normative Islamic theological concepts such as syukr and ukhuwah with anthropological analyses of ritual, symbolism, and collective memory, and thereby advancing interdisciplinary approaches to the study of Islam and local religiosity in Indonesia. Dalam sejarah panjang peradaban Islam di Jawa, tradisi ritual seperti Grebek Besar berfungsi sebagai ruang penting bagi transmisi, reinterpretasi, dan perwujudan nilai-nilai etika dan teologi Islam. Berfokus pada tradisi ini, penelitian ini mengkaji dimensi kultural dan teologis dari festival Grebek Besar di Kabupaten Demak, Jawa Tengah, yang merupakan salah satu perayaan budaya Islam paling signifikan di Jawa. Berakar pada peringatan Iduladha, festival ini merepresentasikan sintesis dinamis antara ajaran Islam dan ekspresi budaya Jawa. Kajian-kajian sebelumnya umumnya memandang Grebek Besar sebagai tradisi folklorik atau peristiwa historis, tanpa menelaah secara memadai makna teoretis teologi yang hidup dalam praktik sosial dan ritual (lived theology) sebagaimana dimaknai oleh aktor-aktor keagamaan lokal dan diwujudkan dalam praktik ritual sehari-hari. Dengan menggunakan pendekatan kualitatif etnografis, penelitian ini didasarkan pada observasi partisipatif, wawancara mendalam dengan tokoh agama dan sesepuh masyarakat, serta analisis arsip dan manuskrip lokal. Temuan penelitian ini dirumuskan dalam satu klaim tematik utama, yaitu bahwa Grebek Besar berfungsi sebagai bentuk teologi Islam yang dihidupi, di mana pertunjukan ritual, objek simbolik, dan partisipasi komunal saling terhubung sebagai mekanisme yang menopang kesalehan religius, kohesi sosial, dan kesinambungan budaya di kalangan Muslim Jawa. Penelitian ini menunjukkan bahwa Grebek Besar bukan sekadar perayaan budaya, melainkan ruang ritual devosional Islam yang tertanam dalam adat lokal. Arak-arakan, doa bersama, dan praktik berbagi makanan mengandung makna teologis yang memperkuat relasi komunitas dengan Tuhan sekaligus meneguhkan memori historis dan identitas kolektif. Penelitian ini memberikan kontribusi ilmiah dengan mengajukan kerangka teoretis lived theology dalam konteks Islam Jawa yang berlandaskan data empiris, dengan menjembatani konsep-konsep teologi Islam normatif seperti syukr dan ukhuwah dengan analisis antropologis mengenai ritual, simbolisme, dan memori kolektif, sehingga memperkaya pendekatan interdisipliner dalam kajian Islam dan religiusitas lokal di Indonesia.